Kekuatan Pembuktian Akta Otentik dalam Perspektif Hukum Acara Perdata (Studi Kasus Putusan Mahkamah Agung No. 656 PK/Pdt/2019) - Yuni Putri Dewantara; Michelle Caroline Hadi; Dave David Tedjokusumo (Universitas Insan Budi Utomo, 2024)
This research aims to examine the role of authentic deeds in determining land ownership. The law recognizes authentic deeds as documents that can be issued by authorized public officials in the local area, with external, formal and material evidentiary powers that make them strong evidence. An authentic deed does not require comparison with other evidence because it contains certainty regarding the recorded facts, including the correct date, time, identity of the parties involved, as well as the signatures of the parties and the notary. Every recorded statement must be correct, however, if there are errors, the notary is not responsible for the contents of the deed, because the notary only records the information provided by the parties. This research uses normative juridical methods and concludes that even though an authentic deed has perfect evidentiary power, its validity and strength can still be questioned, so the deed must be relevant and meet the requirements stipulated in the relevant laws and regulations.